The dynamics of spatial structures in the rural commune of Sourgou (Burkina Faso): an analysis based on ecological indices - Yaya, Maïga; Tiraogo Prince Florian, Bouda Tiraogo Prince Florian; Mahamoudou, Bamogo; Pawendkisgou Isidore, Yanogo; Yélézouomin Stéphane Corentin, Somé (Revue Ecosystèmes et Paysages, 2023)
The land of the rural commune of Sourgou is under anthropic pressure through the extent of rain-fed and irrigated agricultural practices. Its agrarian landscape, like that of other rural communes in Burkina Faso, is changing. The objective of this study is to characterize and evaluate the landscape dynamics of the spatial structures of the rural commune of Sourgou from 2002 to 2021. It was made possible through the application of mainly rural landscape ecology procedures in combination with remote sensing data collection and analysis methods with the 2002 National Topographic Data Base and a 2021 sentinel satellite image. Statistical calculations of indices and areas of the different occupation units as well as the realization of land use maps were carried out. The results show a greater fragmentation (change) of all land use units (savannah, orchards, water surfaces and bare soil) except for rainfed crops which show less fragmentation over the entire study series (2002-2021). Also, the calculation of spatial extension rates shows an evolution of bare soil and water surfaces in the study area at respective rates of 9.21% and 0.73% and a regression of the surface area of savannahs (- 1.45%), orchards (-2.49%) and rainfed crops (-6.00%). Some land use units such as bare soil (0.03 km2), savannah (1.56 km2) and fields (0.99 km2) lost their areas to water surface classes, while orchards (0.37 km2), savannah (18.40 km2), fields (6.66 km2) and watercourses (0.10 km2) converted to bare soil.